A multifunctional hydrogel system with synergistic effects against Staphylococcus aureus infections and inflammation in perioperative cataract surgery - Wendi Zheng; Meiting Lin; Hong Cheng; Xiang Gao; Yongguo Xiang; Wenjuan Wan; Shijie Zheng; Xiaobei Huang; Ke Hu (Materials Today Bio)
Advancing therapeutic strategies with high bioavailability, simplified regimens, and reduced bacterial resistance is crucial for perioperative cataract care. Herein, multifunctional hydrogel eye drops (designated as FQT) were synthesized through a simple one-pot synthesis, employing thermosensitive F127 as the structural scaffold and incorporating quaternized chitosan (QCS) and tannic acid (TA). QCS and TA not only serve as active agents conferring synergistic non-antibiotic antibacterial and anti-inflammatory effects, but also cooperatively interact with F127 through hydrogen bonding, ionic interactions, and electrostatic forces to significantly modulate those hydrogels’ key physicochemical properties, including thermosensitivity, thixotropy, visibility, erosion resistance, and bioavailability. Ultimately, the optimal formulation FQT1/8 (containing 0.125 % w/v TA) was identified, achieving a design optimized for perioperative application in cataract surgery. In rabbit cataract surgery models, FQT1/8 effectively prevented Staphylococcus aureus endophthalmitis from both endogenous and exogenous exposure sources via dual protection mechanisms of physical barriers and high bioavailability, with only once-daily administration. By maintaining low levels of nitric oxide (NO), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) in aqueous humor and the cornea, FQT1/8 significantly suppressed postoperative inflammation. Western blot analysis further demonstrated that FQT1/8 inhibited NF-κB pathway activation by reducing phosphorylated p65 (p-p65) levels and restoring IκBα expression in both rabbit corneal tissues and LPS-stimulated raw264.7 macrophages. Given its noninvasive nature, simple yet composite regimen, and feasibility for clinical translation, FQT1/8 presents a promising approach for perioperative cataract management.